Exploration of the Global Burden of Dementia Attributable to PM2.5: What Do We Know Based on Current Evidence?. (24th May 2021) - Ru, Muye; Brauer, Michael; Lamarque, Jean‐François; Shindell, Drew
Abstract: Exposure to ambient PM2.5 pollution has been linked to multiple adverse health effects. Additional effects have been identified in the literature and there is a need to understand its potential role in high prevalence diseases. In response to recent indications of PM2.5 as a risk factor for dementia, we examine the evidence by systematically reviewing the epidemiologic literature, in relation to exposure from ambient air pollution, household air pollution, secondhand smoke, and active smoking. We develop preliminary exposure‐response functions, estimate the uncertainty, and discuss sensitivities and model selection. We estimate the likely impact to be 2.1 M (1.4 M, 2.5 M; 5%–95% confidence) global incident dementia cases and 0.6 M (0.4 M, 0.8 M) deaths attributable to ambient PM2.5 pollution in 2015. This implies a combined toll from morbidity and mortality of dementia of 7.3 M (5.0 M, 9.1 M) lost disability‐adjusted life years. China, Japan, India, and the United States had the highest estimated total burden, and the per capita burden was highest in developed countries with large elderly populations. Compared to 2000, most countries in Europe, the Americas, and Southern Africa reduced the burden in 2015, while other regions had a net increase. Based on a recent systematic review of cost of illness studies for dementia, our estimates imply economic costs of US$ 26 billion worldwide in 2015. Based on this estimation, ambient PM2.5 pollution may be responsible for 15% of premature deaths and 7% of DALYs associated with dementia. Our estimates also indicate substantial uncertainty in this relationship, and future epidemiological studies at high exposure levels are especially needed. Plain Language Summary: We reviewed the currently available evidence on the linkage between exposures to fine particulate matter and incidence of dementia. With data from these studies, we developed exposure‐response relationships. We quantitatively studied the uncertainty associated with these relationships and examined their robustness. We found high uncertainty, not on the existence of increased risks at increased exposures, but on if and how the risks level off when reaching a relatively higher level of exposures. We used a function that is robust and conservative to produce a preliminary estimate of the global burden of dementia attributable to exposures to fine particulate matter. We found around 2 million cases of dementia incidence likely attributable to such exposure. This implies not only that it would be valuable to better characterize this potentially large risk factor of dementia, but also that there are potential dementia prevention opportunities through air pollution mitigation. Key Points: Our work indicates PM2.5 is a potential risk factor of dementia, but showed high uncertainty with exposure‐response functions We estimate a likely global impact of PM2.5 pollution on dementia to be 2.1 M (1.4–2.5 M) incident cases and 0.6 M (0.4–0.8 M) deaths in 2015 Our study indicates future studies in high‐exposure regions are especially valuable in reducing the uncertainty